2005
DOI: 10.1111/j.1440-169x.2005.00828.x
|View full text |Cite
|
Sign up to set email alerts
|

Extraocular dorsal signal affects the developmental fate of the optic vesicle and patterns the optic neuroepithelium

Abstract: Dorsal-ventral (DV) specification in the early optic vesicle plays a crucial role in the proper development of the eye. To address the questions of how DV specification is determined and how it affects fate determination of the optic vesicle, isolated optic vesicles were cultured either in vitro or in ovo. The dorsal and ventral halves of the optic vesicle were fated to develop into retinal pigment epithelium (RPE) and neural retina, respectively, when they were separated from each other and cultured. In optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 45 publications
7
40
0
Order By: Relevance
“…A signal released from the mesenchyme is thought to be the primary inducer of Mitf expression in the chick and mouse optic vesicle (Fuhrmann et al, 2000;Kagiyama et al, 2005). At stage 9, Mitf expression was seen to be strongest in the distal part of the optic vesicle that is covered by the surface ectoderm (Fig.…”
Section: Bmp Expression During the Initial Stages Of Chick Eye Develomentioning
confidence: 99%
See 2 more Smart Citations
“…A signal released from the mesenchyme is thought to be the primary inducer of Mitf expression in the chick and mouse optic vesicle (Fuhrmann et al, 2000;Kagiyama et al, 2005). At stage 9, Mitf expression was seen to be strongest in the distal part of the optic vesicle that is covered by the surface ectoderm (Fig.…”
Section: Bmp Expression During the Initial Stages Of Chick Eye Develomentioning
confidence: 99%
“…Embryonic transplantations and in ovo explant cultures of the chick optic vesicle have shown that the dorsoventral polarity of the eye is already specified by stage 10 ( Uemonsa et al, 2002;Kagiyama et al, 2005). At this time point, the dorsal half of the optic vesicle is fated to develop mainly into RPE, whereas the ventral portion develops mainly into NR (Kagiyama et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antisense RNA probes specific for chicken Rx (T. Ogura, Tohoku University, Aoba, Japan), Mitf (M. Mochii, University of Hyogo, Japan), Vsx2 and Wnt3a,Wnt4,Wnt5,Wnt5b,Wnt7b,Wnt8b (D. Schulte, Goethe University of Frankfurt/M., Germany) and Wnt2b (H. Roelink, University of Washington, Seattle, WA), were used. In explant cultures of ov, MITF expression was carried out as previously described (Kagiyama et al, 2005;Kobayashi et al, 2010). Human MITF antibody (Sigma-Aldrich, HPA003259), PY489-β-catenin (DSHB), pSmad1/5, pSMAD1/5/8 (Cell Signaling, 9516, 9511S), Retinal pigment epithelial-specific protein 65 kDa (Novus Biologicals, 4018BD113D9) and mouse Pax7 (MAB1675) were used on cryostat sections.…”
Section: In Vivo Electroporationmentioning
confidence: 99%
“…Once NR specification has occurred in the distal ov, Mitf expression becomes restricted to the dorsal ov (Nguyen and Arnheiter, 2000;Nakayama et al, 1998;Müller et al, 2007;Ishii et al, 2009). At this stage, the chick ov is divided into a dorsal RPE and ventral NR domain (Kagiyama et al, 2005;Hirashima et al, 2008;Kobayashi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%